Pendidikan Islam dalam Mencegah Pelecehan Seksual di Era Digital: Analisis Hadis dan Implementasinya dalam Pembentukan Karakater Peserta Didik - Amelia Widjastuti; Romlah Abubakar Askar; Miftahuddin Miftahuddin (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The rapid development of digital technology and social media has transformed patterns of social interaction while simultaneously increasing the risk of sexual harassment in digital spaces. This phenomenon has serious psychological and social impacts, particularly on women and students. Therefore, this study aims to analyze the hadiths related to guarding one's gaze, maintaining proper speech, prohibiting harm to others, and protecting human dignity, as well as examining their relevance in preventing sexual harassment in the digital era through Islamic education. This study employed a qualitative approach with a library research method by analyzing hadith literature, hadith commentaries, and various scholarly works related to digital sexual harassment and Islamic education. The findings reveal that sexual harassment, whether verbal, physical, or digital, contradicts Islamic moral values because it violates human dignity and honor. The hadiths of the Prophet Muhammad provide ethical principles that are highly relevant to contemporary digital life, particularly regarding self-control, respectful communication, and the protection of others' dignity. Furthermore, Islamic education plays a strategic role in preventing sexual harassment through strengthening digital ethics, Islamic social media literacy, and character education among students. This study contributes to the development of hadith studies and Islamic education by offering a contextual understanding of hadith as a moral foundation for addressing contemporary social issues in the digital era.